Actual problems of studying of history of Kursk fight - A. V. Isayev (Vestnik MGIMO-Universiteta)
In article the author addresses to debatable problems of a domestic and foreign historiography of fight near Kursk, pushes together opinions of military historians with memoirs certificates and estimates of battles of World War II of commanders confronting on fields, refers to new documents, defending the judgments. In the author's description of events near Kursk the specified panorama of all military 1943 and its place in the Great Victory of the 1945th opens